THE LOGOEPISTEME AS A PRECEDENT PHENOMENON (Scientific journal of the Fergana State University, 2023)
This article reveals the regularities of logoepistemes as linguocultural units, their deeper meaning, "encryption", and relevance to the reality of each linguoculture, linguocommunity, using numerous examples from journalistic sources. The article also draws attention to the extra-linguistic factors that caused the emergence and use of this phenomenon.